BGP Anomaly Detection Techniques: A Survey - Al-Musawi, Bahaa; Branch, Philip; Armitage, Grenville (IEEE Communications surveys and tutorials, 2017)
The border gateway protocol (BGP) is the Internet's default inter-domain routing protocol that manages connectivity among autonomous systems (ASes). Over the past two decades many anomalies of BGP have been identified that threaten its stability and reliability. This survey discusses and classifies these anomalies and discusses the 20 most significant techniques used to identify them. Our classification is based on the broad category of approach, BGP features used to identify the anomaly, effectiveness in identifying the anomaly and effectiveness in identifying which AS was the location of the event that caused the anomaly. We also discuss a number of key requirements for the next generation of BGP anomaly detection techniques.